The losers in education, work and life chances - the case of Finland - Rinne, Risto [Verfasser]; Järvinen, Tero [Verfasser] (My University, 2010)
"Finland has been remarkably successful in the OECD Programme for International Student Assessment (PISA) studies conducted in the first years of the new millennium. The variation in achievement is low and the educational level of Finnish young people is high in an international comparison. Also, dropout rates are lower in Finland than in many other countries. In this article, the main patterns of post-compulsory graduation and dropping out of education, as well as aspects of social exclusion of Finnish youth are examined. While the overwhelming majority of young people in Finland manage to cope well, an increasing minority seems to be at risk of educational and social exclusion. Establishing educational equality has been at the centre of educational policy in Finland since World War II. However, the current tendency revolves around expediting efficiency and, more generally, serving the economy. These steps towards a neo-liberalistic educational policy threaten to marginalise an ever-growing number of young people from disadvantaged backgrounds and increase the risk of exclusion." (Autorenreferat, BIBB-Doku)
Keywords: S 4.3.5 Bildungsbeteiligung & soziale Gerechtigkeit; G 1.3.2.2.2 Verlauf (Erfolg / Abbruch); S 1.1 Allgemeinbildende Schule; S 1.3 Berufliche Erstausbildung; I 2.2.1 Westeuropa; Bildungsverlauf; Bildungspolitik; Soziale Integration; Schulwesen; Gesamtschule; Schulerfolg; Bildungschance; Berufseinmündung; Ausbildungsabbruch; Benachteiligter Jugendlicher; PISA-Studie; Finnland